Cuantificadores, ejemplo 3 - Chavarría-Molina, Jeffry (My University, 2018)
En este vídeo se presenta un ejemplo de validación de una proposición cuantificada con dos cuantificadores anidados de la forma “existe” “para todo” . En él se da una argumentación que verifica que dicha proposición es falsa.

This video presents an example of validation of a quantified proposition with two nested quantifiers of the form "exists" "for everything". There is an argument that verifies that this proposition is false.
Keywords: Cuantificadores; Matemáticas discretas; Validación; Verificación; Quantifiers; Validation; Discrete mathematics; Verification